Nanoformulation of Polymyxin E Through Complex Coacervation: A Pharmacokinetic Analysis - Xiaobao Chen; Li Liu; Weidan Wang; Yuan Yuan; Wei Wang (Pharmaceutics)
Objectives: Polymyxin E (PME), a polymyxin antibiotic, serves as a final resort against antibiotic resistance. Nephrotoxicity is the primary concern when employing PME. To alleviate this issue, researchers have explored strategies including dosing adjustments and innovative formulations. This study employed complex coacervation to create PME nanoformulations, capitalizing on PME’s charge properties. The research question and hypothesis posed pertained to whether neutralization of PME’s positive charge during formulation would reduce its antibiotic efficacy and alter its tissue distribution and other pharmacokinetic parameters. Our objective was to evaluate the capability of complex coacervation to mitigate the adverse effects of PME while preserving its antibacterial potency and therapeutic effectiveness. Methods: Three negatively charged polyions: potassium sucrose octasulfate, polytamic acid, and sodium hyaluronate, were used for formulation. We performed characterization on the nanocomplex formed by the polyions and PME. The nanoformulations underwent several tests, including minimum inhibitory concentration, in vivo efficacy on an infected mouse model, pharmacokinetic assessments, tissue distribution, and toxicity. Results: the three polyions formed coacervation complexes with PME at varying charge ratios, yielding nanoparticles smaller than 30 nm with low polydispersity (PDI < 0.3). The results demonstrated that complex coacervation-mediated PME nanoformulations exhibited equivalent or superior antibacterial activity, increased maximum tolerant dose, and fewer adverse reactions in animal tests. Conclusions: Utilizing complex coacervation, PME nanoformulations were developed, demonstrating efficacy in the formulation process. Pharmacokinetic assessments revealed absorption and distribution profiles akin to those of standalone PME. The positive charge inherent in PME causing its toxicity was mitigated after complex coacervation.